Effects of dietary supplementation with icariin on growth performance, antioxidant capacity and non-specific immunity of Chinese mitten crab (Eriocheir sinensis). Issue 90 (July 2019) - Zheng, Xiaochuan; Chi, Cheng; Xu, Chenyuan; Liu, Jiadai; Zhang, Caiyan; Zhang, Ling; Huang, Yangyang; He, Chaofan; He, Chang; Jia, Xiaoyan; Liu, Wenbin
Abstract: We investigated the effects of icariin (ICA) on growth performance, antioxidant capacity and non-specific immunity in Chinese mitten crab ( Eriocheir sinensis ). A total of 200 healthy crabs (average weight: 33.58 ± 0.05 g) were randomly assigned to four treatments with five replicates, each with ten individuals per pool. There were four dietary treatments: the control group (fed with the basal diet), the ICA 50 group, the ICA100 group, and the ICA 200 group (fed with the basal diet supplemented with 50, 100, and 200 mg/kg ICA, respectively). These diets were provided for 8 weeks. Results indicated that ICA100 crabs had higher weight gain (WG), specific growth rate (SGR) and survival rate (SR) than the controls. Protein carbonyl content (PCC) and malondialdehyde (MDA) concentrations in the haemolymph and hepatopancreas of ICA100 crabs were significantly lower than in the control group, while the superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities were significantly higher. The activities of PO, LZM, ACP and AKP were significantly enhanced with ICA supplementation at 50 and 100 mg/kg, yet decreased subsequently at 200 mg/kg. Furthermore, supplementation of 100 mg/kg ICA up-regulated the mRNA expression of prophenoloxidase ( proPO ), catalase ( CAT ), mitochondrial manganese superoxide dismutase ( mtMnSOD ), thioredoxin-1 ( Trx1 ) and peroxiredoxin 6 ( Prx 6), while the mRNA expression of toll like receptors ( TLRs ), NF-κB-like transcription factor Relish and lipopolysaccharide-induced TNF-α factor ( LITAF ) were down-regulated in the hepatopancreas ( P < 0.05 ). These findings indicate that dietary ICA supplementation at an optimum dose of 100 mg/kg may be effective in improving growth performance, antioxidant capability and non-specific immunity of Chinese mitten crab. Highlights: The optimal icariin (ICA) level for Eriocheir sinensis was 100 mg/kg. ICA supplementation significantly affects antioxidant and non-specific immunity. Crabs fed with 100 mg/kg ICA had the highest WG, SGR and SR. ICA supplementation enhanced activities of antioxidant and immune-related enzymes. Dietary ICA supplementation positively regulated the immune-related genes expression.